2017
DOI: 10.1038/srep44382
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Belowground Microbial Composition, Diversity and Activity to Soilborne Disease Suppression and Growth Promotion of Tomato Amended with Biochar

Abstract: Biochar, in addition to sequestering carbon, ameliorating soil, and improving plant performance, can impact foliar and soilborne plant diseases. Nevertheless, the mechanisms associated with suppression of soilborne diseases and improved plant performances are not well understood. This study is designed to establish the relationships between biochar-induced changes in rhizosphere microbial community structure, taxonomic and functional diversity, and activity with soilborne disease suppression and enhanced plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(127 citation statements)
references
References 81 publications
10
107
0
1
Order By: Relevance
“…This demonstrated that biochar amendment altered soil microbial composition in Moso bamboo forests, which concurs with Khodadad et al (2011) and Perry et al (2015). Jaiswal et al (2017) observed a significant decrease in Acidobacteria abundance in the biochar-enriched soil rhizosphere. Acidobacteria generally prefer oligotrophic environments and lower pH soils; therefore, it is possible that the reduction in Acidobacteria was a response to the biochar-related shift to a more neutral and copiotrophic environment (Jaiswal et al 2017).…”
Section: Effects Of Biochar Amendmentsupporting
confidence: 74%
See 1 more Smart Citation
“…This demonstrated that biochar amendment altered soil microbial composition in Moso bamboo forests, which concurs with Khodadad et al (2011) and Perry et al (2015). Jaiswal et al (2017) observed a significant decrease in Acidobacteria abundance in the biochar-enriched soil rhizosphere. Acidobacteria generally prefer oligotrophic environments and lower pH soils; therefore, it is possible that the reduction in Acidobacteria was a response to the biochar-related shift to a more neutral and copiotrophic environment (Jaiswal et al 2017).…”
Section: Effects Of Biochar Amendmentsupporting
confidence: 74%
“…Jaiswal et al (2017) observed a significant decrease in Acidobacteria abundance in the biochar-enriched soil rhizosphere. Acidobacteria generally prefer oligotrophic environments and lower pH soils; therefore, it is possible that the reduction in Acidobacteria was a response to the biochar-related shift to a more neutral and copiotrophic environment (Jaiswal et al 2017). Xu et al (2014) found that biochar amendment in an acidic soil (pH 4.48) changed the relative abundance of some microbes that are related to C and N cycling.…”
Section: Effects Of Biochar Amendmentmentioning
confidence: 81%
“…In vitro assays using BCHs produced from eucalyptus wood (600 ÂșC) and pepper residues (350 ÂșC), when added at different concentrations (0, 0.5, 1, and 3%) to the culture medium, did not inhibit mycelial growth of the phytopathogen Fusarium oxysporum f. sp. radicis lycopersici compared to the unmodified control (without biochar), indicating that for the tested pathosystem the direct effect of biochar cannot be considered a mechanism of disease suppression [20].…”
Section: Resultsmentioning
confidence: 91%
“…Similarly, the application of biochar from eucalyptus wood (600 ÂșC) to the soil resulted in a decrease of up to 61% in fusarium wilt in tomato plants, just as plants cultivated in soil without biochar showed wilt symptoms one day before those containing biochar [20]. The authors emphasized that application of biochar to the soil stimulated rhizospheric microbial diversity related to the genera known for promoting plant growth, suppressing diseases, possible ecological roles (decomposition of organic compounds) and biological nitrogen fixation.…”
Section: Resultsmentioning
confidence: 99%
“…produce complex compounds that are antagonistic toward many fungal pathogens and also have antibiotic properties (Chernin et al, 1995(Chernin et al, , 1996. Neisseria is associated with disease suppressive soils (Almario et al, 2013;Adam et al, 2014), Peredibacter suppresses soil-borne disease (Jaiswal et al, 2017), and Pseudomonas induces systemic resistance against pathogens such as the soil-borne Rhizoctonia solani (Nandakumar et al, 2001). Streptosporangium is an Actinomycete known to produce antimicrobial compounds (Hardoim et al, 2015).…”
Section: B Napus Genotype Regulated Changes In Rhizosphere Bacteriamentioning
confidence: 99%